Alternative Complement Pathway in Carotid Atherosclerosis: Low Plasma Properdin Levels Associate With Long‐Term Cardiovascular Mortality - Mieke C. Louwe; Chrysostomi Gialeli; Annika E. Michelsen; Sverre Holm; Andreas Edsfeldt; Karolina Skagen; Tove Lekva; Maria Belland Olsen; Vigdis Bjerkeli; Therese Schjørlien; Kristine Stø; Xiang Yi Kong; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Complement activation may promote atherosclerosis. Yet, data on the to which extent complement, and more specifically the alternative complement pathway, is activated in patients with carotid atherosclerosis and related to adverse outcome in these patients, are scarce. Methods and Results We measured, by ELISA, plasma levels of factor D, properdin, C3bBbP (C3 convertase), and factor H in patients with advanced carotid atherosclerosis in a Discovery (n=324) and in a Validation (n=206) cohort in relation to adverse outcome (mean follow‐up 7.8 and 6.6 years, respectively). Our major findings were as follows. Compared with healthy controls, patients with carotid atherosclerosis had increased plasma levels of factor D, properdin, and C3bBbP (P<0.001), but not factor H, an inhibitor of the alternative complement pathway, compared with controls. Although patients with carotid atherosclerosis had elevated levels of properdin compared with controls, within these patients, low plasma levels of properdin (ie, <median levels of properdin in the patient group) were significantly associated with cardiovascular mortality. This was seen in both the Discovery (HR 2.31, P=0.019) and the Validation cohort (hazard ratio [HR], 2.81, P=0.014). In contrast to the low circulating levels, high intraplaque properdin levels (assessed by ELISA) correlated with markers of plaque vulnerability and symptomatology. Conclusions We show a strong and independent association of low plasma properdin levels with cardiovascular mortality in 2 cohorts. Conversely, the plaque properdin levels linked to features of plaque vulnerability, potentially reflecting increased deposition at the site of inflammation or local production of properdin in the atherosclerotic lesion indicating local enhanced alternative complement pathway activation.